Clinical Features and Genetic Spectrum of Patients With Clinically Suspected Hereditary Progressive Spastic Paraplegia - Shi, Yuzhi; Wang, An; Chen, Bin; Wang, Xingao; Niu, Songtao; Li, Wei; Li, Shaowu; Zhang, Zaiqiang (Frontiers in Neurology, 2022)
Background and Purpose: A variety of hereditary diseases overlap with neurological phenotypes or even share genes with hereditary spastic paraplegia (HSP). The aim of this study was to determine the clinical features and genetic spectrum of patients with clinically suspected HSPs. Methods: A total of 52 patients with clinically suspected HSPs were enrolled in the study. All patients underwent next generation sequencing (NGS) and triplet repeat primed PCR to screen for the dynamic mutations typical of spinocerebellar ataxia (SCA). Multiplex ligation-dependent probe amplification (MLPA) was further conducted in patients with no causative genetic mutations detected to examine for large deletions and duplications in genes of SPAST, ATL1, REEP1, PGN, and SPG11. Clinical characteristics and findings of brain magnetic resonance imaging (MRI) findings were analyzed in patients with definite diagnoses. Results: The mean age of the patients studied was 36.90±14.57 years. Seventy-five percent (39/52) of patients manifested a phenotype of complex form of HSPs. A genetic diagnosis was made in 51.9% (27/52) of patients, of whom 40.3% (21/52) had mutations in HSPs genes (SPG4/SPG6/SPG8/SPG11/SPG15/SPG78/SPG5A) and 11.5% (6/52) had mutations in SCAs genes (SCA3/SCA17/SCA28). SPG4 and SPG11 was the most common cause of pure form of HSPs (5/6, 83.3%) and complex form of HSPs (5/15, 33.3%), respectively. Gait disturbance was the most common initial symptom in both patients with HSPs (15/21) and in patients with SCAs (5/6). Dysarthria and cerebellar ataxia were detected in 28.5% (6/21) and 23.8% (5/21) of patients with HSPs respectively, and were the most common symptoms in addition to progressive weakness and spasticity of the lower limbs. Cerebellar atrophy was seen on the brain MRI of patients with SPG5A, SCA3 and SCA28. Conclusion: Causative genetic mutations were identified 51.9% of patients with clinically suspected HSPs by NGS and triplet repeat primed PCR. A final diagnosis of HSPs or SCAs was made in 40.3% and 11.5% of patients, respectively. The clinical manifestation and neuroimaging findings overlapped between patients with HSPs and patients with SCAs. Dynamic mutations should be screened in patients with clinically suspected HSPs, especially in those with phenotypes of complex form HSPs.